2020
DOI: 10.3390/cells9051104
|View full text |Cite
|
Sign up to set email alerts
|

Succinate Activates EMT in Intestinal Epithelial Cells through SUCNR1: A Novel Protagonist in Fistula Development

Abstract: The pathogenesis of Crohn’s disease-associated fibrostenosis and fistulas imply the epithelial-to-mesenchymal transition (EMT) process. As succinate and its receptor (SUCNR1) are involved in intestinal inflammation and fibrosis, we investigated their relevance in EMT and Crohn’s disease (CD) fistulas. Succinate levels and SUCNR1-expression were analyzed in intestinal resections from non-Inflammatory Bowel Disease (non-IBD) subjects and CD patients with stenosing-B2 or penetrating-B3 complications and in a muri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 42 publications
(52 reference statements)
1
35
0
Order By: Relevance
“…We evaluated the effects of the VDR gene on the human intestinal epithelial tumor cell line HT29 by establishing a well-characterized model of TGF-β1-induced EMT ( 27 , 28 ). In HT29 cells, knockdown of VDR expression decreased epithelial integrity ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We evaluated the effects of the VDR gene on the human intestinal epithelial tumor cell line HT29 by establishing a well-characterized model of TGF-β1-induced EMT ( 27 , 28 ). In HT29 cells, knockdown of VDR expression decreased epithelial integrity ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the first study, the authors reported a significant increase in succinate in CD patients compared with control subjects [17]. In addition, in a second study, the same authors expanded their observations, and they have recently reported that succinate levels are even increased in CD patients with a penetrating behaviour (B3-CD patients) compared with CD patients with a stricturing behaviour (B2-CD patients) [18]. This difference in one TCA cycle intermediate reveals the importance of studying the metabolomic patterns specifically in intestinal resections of IBD patients.…”
Section: Metabolite Alterationmentioning
confidence: 91%
“…Remarkably, it has become evident over the last decade that succinate also functions as an extracellular signaling metabolite via engagement with its cognate receptor succinate receptor 1, SUCNR1 (also known as GPR91). While its role in cancer has been poorly studied, SUCNR1 has been proposed as a tumor driver, as succinate-SUCNR1 signaling has been related to epithelial-to-mesenchymal transition [ 14 ], angiogenesis [ 15 ] and tumor-associated macrophage polarization [ 16 ]. Moreover, SUCNR1 expression seems to be closely related to immune status in ovarian cancer [ 17 ].…”
Section: Introductionmentioning
confidence: 99%